A Unilateral Variation in Triceps Brachii Muscle Demonstrating a Fourth Head - Swami, Shveta; Budhiraja, Virendra; Sharma, Deepak; Gupta, Rimpi; Bansal, Swati (Annals of the National Academy of Medical Sciences (India), 2021)
Introduction Triceps brachii muscle is the only muscle of posterior compartment of arm, consisting of three heads—long, lateral, and medial. Radial nerve and profunda brachii artery run in the radial groove that separate lateral and medial head. Evolutionarily, triceps has many subheads which either fused or disappeared. Therefore, the knowledge of muscle is essential anthropologically and clinically, and this study aims to study the anatomical variations of triceps brachii muscle.Case Report In the present case, during routine dissections of undergraduate MBBS students, a fourth head of origin of triceps brachii muscle was seen in a male cadaver in the right arm. The variation was seen only unilaterally in cadaver. The origin was tendinous arising from the posteromedial aspect of upper part of the shaft of the humerus close to the surgical neck above the radial groove. This tendon was arching over the neurovascular bundle containing radial nerve and profunda brachii artery.Discussion and Conclusion The variations of triceps brachii muscles are mentioned in literature but are uncommon and if tendinous fourth head is present over the neurovascular bundles, it may lead to compression syndrome. Hence, these variations are of great importance to the radiologists, surgeons, and orthopaedicians while dealing with posterior compartment of arm.
Keywords: triceps brachii; variations; fourth head; neurovascular bundle; compression syndrome